INFLUENCE OF WOOD YIELD ESTIMATIONS IN FOREST REGULATION PROCESSES USING LINEAR PROGRAMMING - Silva, Gilson Fernandes da (2005)
The main objective of this work was to evaluate the consequences of the use of yield and growth estimates from different prediction yield and growth models in a Linear Programming model applied to forest regulation. Thus, using data of continuous forest inventory, the yield estimation in future volume was obtained using a yield model based on age, another one based on age and site index, and a third model that used age and site index besides density, which was represented by the basal area per hectare. Also a model based on data of continuous forest inventory which uses data of volume on a period of time to make linear projections of yield for the next period was tested. Next, a simplified forest regulation problem was proposed and solved by the model I by means of Linear Programming, using data from the four volume prediction models. At the end, the conclusion was: a) that models of forest regulation, supplied with estimates from different yield models, when solved by Linear Programming, result in different ways of treating the forests; b) that the matrix of technological coefficients, supplied with different yield data and for a same objective function affects in a significant way the decision making process.